Analisis Strategi Manajemen Pemasaran Pendidikan dalam Menarik Minat Peserta Didik - Ilham Afif; Mohammad Aquallurrizal; Arza Lubaib Almuna; Farchatul Maru`ah (Jurnal Bintang Pendidikan Indonesia, 2026)
This study was conducted based on observational findings indicating that educational institutions need to implement appropriate educational marketing management strategies to enhance their attractiveness amid increasing competition. The purpose of this study is to analyze educational marketing management strategies used to attract prospective students and to identify factors influencing their effectiveness. This research employed a qualitative approach, with observation, interviews, and documentation serving as data collection techniques. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that educational marketing strategies are implemented through promotional program planning, utilization of information media, improvement of educational service quality, strengthening of institutional image, and collaboration between schools and the community. A well-planned and sustainable marketing system has been shown to increase public trust in educational institutions. Furthermore, students’ interest in choosing an educational institution is influenced by the quality of educational programs, supporting facilities, school reputation, learning environment, and information accessibility through various media. The study findings indicate that effective implementation of educational marketing management strategies can enhance institutional competitiveness and increase student enrollment. Therefore, educational institutions are encouraged to continuously develop innovative marketing strategies that align with community needs to remain relevant and attractive to prospective students.